Crise de l’État et territoires de la crise au Mali - Hawa Coulibaly; Stéphanie Lima (EchoGéo)
This article focuses on the territorial dimensions of the socio-political and territorial crisis in Mali since the military coup took place in March 2012. Mali's news is dominated by an unprecedented crisis in the country's history, deep and complex. Despite innovative decentralization, recurrent tensions, whose origins date back to colonization between local societies and the central government persist in this country though it was now the last twenty years a "good student" of democratization. The objective of this paper is to reconsider the relationship between power and territory, through the prism of successive divisions of the national territory. How to explain the collapse of the country house and the undermining of national unity? What are the reason why the state has collapsed on itself?